Comparative Analysis of Moral Action in Sociological Theories of Vytautas Kavolis and Émile Durkheim - Varnauskaitė, Laura (Sociologija. Mintis ir veiksmas, 2013)
The article analyses the moral action to reveal the elements of tension and interaction between the individual and the society by comparing theories of Vytautas Kavolis and of Emile Durkheim. Social action and moral action are different analytical categories. The problem arises when it is necessary to establish links between these concepts. The article is based on the position that moral action and social action has a relation as part and a whole, has a different study objects, but obeys the same study method. According to Durkheim‘ s definitions of social fact and of moral fact, social fact is a broader category that includes the moral facts. It is shown that the facts includes social phenomena feathuring the expediency of performed actions of individuals. Therefore, social action is interpreted by adapting the definition of a social fact, as appropriate, moral action is interpreted by definition of moral fact. The aim is to identify the characteristics, conditions, and factors of moral action. Theories of moral action of Durkheim and of Kavolis are analyzed. French sociologist distinguishes social power to encourage an individual to behave in one way or another. Durkheim indicates that the social power works in society as in individuals by using an association method. Kavolis emphasizes the inner imperative which is a basis for moral action, arising from the conscious individual, performed after internalisation of moral principle itself. However, the individual and society have different goals. An individual seeks to realize the freedom as creative potential. The society requires the individual to obey historically formed norms and rules of conduct. On the other hand, the individual performing a moral action is always influenced by the social environment and his actions always have social impact.